Localization of Lyme disease spirochetes Borrelia burgdorferi in ticks Ixodes ricinus - Strnad, Martin (Jihočeská univerzita, 2013)
Lyme disease is the most common vector-borne infection in the Western world with an annual incidence usually in excess of 100 cases per 100 000 people in temperate areas of the United States and Europe. Same as other infectious diseases, Lyme borreliosis wreaks havoc on the host they have invaded. B. burgdorferi, the causative agent of this disease, circulates among wildlife vertebrate hosts and Ixodes tick vectors but may sometimes infect humans. Its natural enzootic cycle usually occurs as follows: The larval/nymphal stage tick feeds on an infected host. During this engorgement, the spirochetes reach the tick gut and stay confined to it. After the tick molts into the next developmental stage, it finds a second host. The new bloodmeal triggers the spirochetes to multiply within the gut and traverse the gut endothelium in a highly organized manner. They finally disseminate through the hemocoel up to the tick salivary glands and into the new host. We studied whether B. burgdorferi is capable of reaching the tick salivary glands during the first infective feeding period in uninfected ticks.
Localization of Lyme disease spirochetes Borrelia burgdorferi in ticks Ixodes ricinus
Keywords: Ixodes ricinus; Borrelia burgdorferi; in-vitro feeding; fluorescence and electron microscopy; Ixodes ricinus; Borrelia burgdorferi; in-vitro feeding; fluorescence and electron microscopy